DAMPAK SOSIAL EKONOMI TRAGEDI SITU GINTUNG - Azhar Firdaus; Muhammad Zahran Al Ariq (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2023)
When in 2009 the Situ Gintung lake collapsed because it was no longer strong enough to hold the overflow of water in it, many sociological and economic aspects of society changed. The research found several socio-economic implications, namely: at work there are various changes, namely people cannot take advantage when opening a business. In social institutions, namely the formation of the Situ Gintung Forum. Solidarity between residents mostly occurs when there are social activities in their environment, and what is discussed is only complaints about the Situ Gintung tragedy. As well as the value system, namely that people understand each other when a resident is affected by adisaster, and only people who live permanently can continue their education to a higher level.